Prognosis of patients with bilateral fixed dilated pupils secondary to traumatic extradural or subdural haematoma who undergo surgery: a systematic review and meta-analysis. Issue 8 (10th November 2014) - Scotter, John; Hendrickson, Susan; Marcus, Hani J; Wilson, Mark H
Abstract : Primary objective: To review the prognosis of patients with bilateral fixed and dilated pupils secondary to traumatic extradural (epidural) or subdural haematoma who undergo surgery. Methods: A systematic review and meta-analysis was performed using random effects models. The Cochrane Central Register of Controlled Trials and PubMed databases were searched to identify relevant publications. Eligible studies were publications that featured patients with bilateral fixed and dilated pupils who underwent surgical evacuation of traumatic extra-axial haematoma, and reported on the rate of favourable outcome (Glasgow Outcome Score 4 or 5). Results: Five cohort studies met the inclusion criteria, collectively reporting the outcome of 82 patients. In patients with extradural haematoma, the mortality rate was 29.7% (95% CI 14.7% to 47.2%) with a favourable outcome seen in 54.3% (95% CI 36.3% to 71.8%). In patients with acute subdural haematoma, the mortality rate was 66.4% (95% CI 50.5% to 81.9%) with a favourable outcome seen in 6.6% (95% CI 1.8% to 14.1%). Conclusions and implications of key findings: Despite the poor overall prognosis of patients with closed head injury and bilateral fixed and dilated pupils, our findings suggest that a good recovery is possible if an aggressive surgical approach is taken in selected cases, particularly those with extradural haematoma. Trial registration number: CRD42013005198.